Attacks on practical quantum key distribution systems (and how to prevent them). Issue 3 (2nd July 2016) - Jain, Nitin; Stiller, Birgit; Khan, Imran; Elser, Dominique; Marquardt, Christoph; Leuchs, Gerd
Abstract : With the emergence of an information society, the idea of protecting sensitive data is steadily gaining importance. Conventional encryption methods may not be sufficient to guarantee data protection in the future. Quantum key distribution (QKD) is an emerging technology that exploits fundamental physical properties to guarantee perfect security in theory. However, it is not easy to ensure in practice that the implementations of QKD systems are exactly in line with the theoretical specifications. Such theory–practice deviations can open loopholes and compromise security. Several such loopholes have been discovered and investigated in the last decade. These activities have motivated the proposal and implementation of appropriate countermeasures, thereby preventing future attacks and enhancing the practical security of QKD. This article introduces the so-called field of quantum hacking by summarising a variety of attacks and their prevention mechanisms.